FINANCING STRATEGY FOR BUILDING A NICKEL SMELTER, BY IMPLEMENTING BOT SCHEME. (CASE STUDY: PT. TOMINDO ENERGY, HALMAHERA, CENTRAL MALUKU) (The Indonesian Journal of Business Administration, 2019)
The globalization of production and distribution has required countries to have efficient infrastructure in order to be able to have substantial participation in global trading and production networks.  Since the early 1990s, the mining sector has reopened to invest in it, Indonesia has increased its rank in production, domestic coal sales, and for coal exports. Indonesia is very profitable because of its wealth, geographically strategic to emerging markets, thus the demand for low-quality coal from developing countries has increased sharply. PT. Tomindo will build a smelter plant in Central Halmahera, North Maluku. Building a new smelter in order to meet the increasing market demand and will enter the company's assets. PT. Tomindo collaborates using BOT Scheme to carry out the new smelter plant construction project. Investors and PT. Tomindo will use the BOT scheme to shall establish a smelter, which investors have comprised of finance, design, procurement, construction, testing commissioning operation and maintenance including auxiliary equipment and supporting facilities for operating a reliable base. The methodology used of this research is to know the business issue, and then analyze the situation if this company build a new smelter plant. Through the external analysis using PESTEL (Politic Economic, Social, Technology, Environment and Legal) and Porter’s Five Forces, and then to internal analysis using Research and Capabilities analysis. After that, analyzing the external and internal aspects of the company, a SWOT analysis is performed, also obtained using TOWS matrix analysis. Then to the calculation of the Financial Projection and Financial Feasibility Study of the project to be carried out. After getting the results of the calculations carried out NPV, IRR and Payback Period. Entire the project financing use 70% loan and 30% equity with the life time of project 10 years. From the calculation of the Financial Feasibility Study results the Payback Period from this project is for 1,54 years, the result of Net Present Value (NPV) is positive by 3.605.239.070,86 USD, and the Internal Rate of Return (IRR) is 21,53%% which is greater than the Weighted Average Cost of Capital (WACC) of 5,98%. Based on the calculation, it can be seen that this project is financially feasible, this is because the result shows that all indicators are acceptable. Keyword: BOT Scheme, Capital Budgeting, Coal and mining Industry, Feasibility Study.